"Let Us Continue Free as the Air": Truthfully Reconciling Social Work Education to Indigenous Lands. (3rd July 2018) - Leduc, Timothy B.
ABSTRACT: Social work is being challenged to situate its theories and practice within the lands it finds itself on in North America. This article considers the Canadian Truth and Reconciliation Commission's calls for change from the perspective of how social workers are educated in relation to land, from Indigenous views on its colonial conversions to the land's role in healing. The discussion is grounded in a course I teach on Reconciliation and Indigenous-Social Work Relations on the Haudenosaunee lands of the Grand River in Ontario. Social work students consider their vocation in relation to a truth-telling process that is a first step for reconciling with Indigenous nations and land. The article concludes with general implications for social work educators.